2017
DOI: 10.1111/bjd.15618
|View full text |Cite
|
Sign up to set email alerts
|

Variants at theOCA2/HERC2locus affect time to first cutaneous squamous cell carcinoma in solid organ transplant recipients collected using two different study designs

Abstract: Background Variants at the Oculocutaneous albinism 2 (OCA2)/HECT and RLD Domain Containing E3 Ubiquitin Protein Ligase 2 (HERC2) locus have been associated with pigmentation phenotypes as well as risk of developing multiple types of skin cancer. Objectives The goal of this study was to evaluate OCA2/HERC2 locus variants for impact on time to develop cutaneous squamous cell carcinoma (cSCC) in organ transplant recipients (OTRs) who are at elevated risk of developing cSCC. Methods Participants were solid org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…One area where PRS may show particular value is in improving risk stratification for OTRs. Fitzpatrick skin phototype and polymorphisms in the OCA2 / HERC2 and IRF4 pigmentation genes have been associated with development of post‐transplant cSCC . Additional research is needed to determine whether PRS can improve risk prediction above established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…One area where PRS may show particular value is in improving risk stratification for OTRs. Fitzpatrick skin phototype and polymorphisms in the OCA2 / HERC2 and IRF4 pigmentation genes have been associated with development of post‐transplant cSCC . Additional research is needed to determine whether PRS can improve risk prediction above established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of HERC2 , affecting stabilization and chromatin retention of XP complementation group A (XPA), might also be involved in cutaneous SCC. [ 13 , 14 ] XPA is controlled by circadian clock-mediated transcriptional regulation, while the ubiquitination mediated by homologous to the E6-AP carboxyl terminus domain and RCC1-like domain-containing protein 2 (HERC2), which leads to XPA's degradation, could also contributes to the circadian oscillation. [ 14 ] A recent study, in addition, reported variants at the OCA2/HERC2 locus have strong association between time to first cutaneous SCC post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a preliminary study, Wei et al . demonstrate that risk prediction models can be extended to incorporate a transplant patient's genetic susceptibility to cSCC to better identify individuals at higher risk of early cSCC development post‐transplant and tailor screening intensity.…”
mentioning
confidence: 99%
“…Wei and colleagues report findings combining data from two observational cohorts of solid organ transplant recipients (OTRs) at different medical centres showing that OCA2/HERC2 locus variants impact the time to first cutaneous squamous cell carcinoma (cSCC) post‐transplant . OTRs with two blue‐eye‐associated alleles for OCA2/HERC2 , variants rs916977 and rs12913832, each had an estimated median time to first cSCC of 14·2 years post‐transplant, which was 12·3 and 7·4 years earlier, respectively, compared with OTRs with two corresponding brown‐eye‐associated alleles.…”
mentioning
confidence: 99%